2012
DOI: 10.1007/s00726-012-1392-x
|View full text |Cite
|
Sign up to set email alerts
|

On the role of the mitochondrial 2-oxoglutarate dehydrogenase complex in amino acid metabolism

Abstract: Mitochondria are tightly linked to cellular nutrient sensing, and provide not only energy, but also intermediates for the de novo synthesis of cellular compounds including amino acids. Mitochondrial metabolic enzymes as generators and/or targets of signals are therefore important players in the distribution of intermediates between catabolic and anabolic pathways. The highly regulated 2-oxoglutarate dehydrogenase complex (OGDHC) participates in glucose oxidation via the tricarboxylic acid cycle. It occupies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 57 publications
2
54
0
Order By: Relevance
“…Thus, the “dab2 interacting protein” ( dab2ip ) gene, which suppresses the development of many cancer types [43], likely appeared among the SH genes for this reason. Meanwhile, some genes relevant to energy metabolism, for example, the “2-oxoglutarate dehydrogenase” ( ogdh ) [44] and atp6v0a1 genes, participate in the “oxidative phosphorylation” pathway and probably contributed to adaptation to the reduced water temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the “dab2 interacting protein” ( dab2ip ) gene, which suppresses the development of many cancer types [43], likely appeared among the SH genes for this reason. Meanwhile, some genes relevant to energy metabolism, for example, the “2-oxoglutarate dehydrogenase” ( ogdh ) [44] and atp6v0a1 genes, participate in the “oxidative phosphorylation” pathway and probably contributed to adaptation to the reduced water temperature.…”
Section: Resultsmentioning
confidence: 99%
“…We thus speculate that sugar analogs that are unable to be utilized by A. flavus are candidate inhibitors for AF biosynthesis. Chemical analogs are often used to inhibit metabolism, as they may bind competitively to the active or allosteric sites of enzymes and hamper their activities [10,11]. Three glucose analogs, 2-deoxyglucose, α-methyglucoside and glucosamine, have been tested in A. parasiticus previously, but none of them inhibited AF production when applied to a glucose-containing medium [12].…”
Section: Introductionmentioning
confidence: 99%
“…As examples, upregulation of OGDH was identified as a driver for hepatocellular carcinoma29. Recent studies also reported that targeting the α-KGDH complex inhibits amino-acid metabolism and regulates oxidative stress in cancer cells1330. Inhibition of OGDH leads to buildup of lactic acid and suppresses cell growth1531.…”
mentioning
confidence: 99%